PECULIAR TEMPERATURE REGIME IN COLD FROZEN SOILS ALONG THE SOUTHERN BOUNDARY OF THE CRYOLITHOZONE IN THE NORTH-EAST OF EUROPEAN RUSSIA - D. A. Kaverin; A. V. Pastukhov; G. G. Mazhitova (Бюллетень Почвенного института им. В.В. Докучаева)
Under study was the temperature regime of frozen soils situated along the southern boundary of cryolithozone in the North-East of European Russia. In southern tundra the frozen soils with the cold temperature regime are confined to peat and mineral parent materials. The seasonal and long-term temperature dynamics in seasonal-thawing and underlying permafrost-affected layer is shown. The frozen soils are characterized by the main temperature indices.